Employees’ Work-Life Balance and Career Contentment in a Philippine Local Government Unit - Bryle Jhon W Concepcion; Lemuelle Bea O Cruz; Anne Lorraine A Chavez; Jesus P Briones; Marmelo V Abante (Applied Quantitative Analysis, 2024)
Work-life balance (WLB) is crucial for employee well-being and career satisfaction, particularly among government employees. This study examined the relationship between WLB and career contentment within the Philippine Local Government Unit (LGU), assessed the levels of both factors, explored their interaction, and recommended strategies to enhance WLB. Using a quantitative-descriptive research method, data were collected from 133 employees from a Philippine LGU through an adapted questionnaire formatted in Google Forms and distributed via electronic mail and Messenger. The data were analyzed using frequency, percentage, weighted mean, standard deviation, and linear regression. Findings revealed that the WLB level among Philippine LGU employees is high. Moreover, the study also showed that LGU employees are generally contented with their careers. However, the findings also suggest no significant relationship between the two variables, where improvements in WLB may not always align with increased career contentment, although job satisfaction and performance are presumably enhanced. The road map strategy proposed by the researchers is recommended as a guide to improve WLB, thereby enhancing employee satisfaction and LGU employee performance. The study findings are significant because they shed light on the intricate relationship between WLB and career contentment within a specific context, thus offering valuable insights for Filipino LGUs. Thus, this study can serve as a reference for public sector organizations that prioritize the well-being of their employees and seek to further improve the workplace environment for more engaging and productive employees.